Energy migration effect on the formation mechanism of different unsaturations in ethylene/styrene random copolymers. (February 2019) - Ferry, M.; Ramillon, J.M.; Been, T.; Lutz, P.J.; Ngono-Ravache, Y.; Balanzat, E.
Abstract: To evaluate the influence of specific parameters, i.e. energy sink concentration and excitons and/or radical migration, on the mechanisms underlying the formation of double bonds in aliphatic polymers, materials with energy sinks in the chain were synthesized. By following the radiation-induced modifications in ethylene/styrene random copolymers, as a function of the styrene content and of the irradiation temperature, we were able to understand the formation mechanisms of trans- vinylenes, trans-trans- dienes, allyl radicals and vinyls. The irradiation temperature allows the discrimination between energy transfers (at 11 K and at room temperature, RT) and of radical migration (at RT). Irradiations were performed using swift heavy ions, and we could show that track overlapping has also an influence on the studied chemical group concentrations. For instance, trans- vinylenes are influenced by excitation transfer and radical migration: their formation decreases in presence of styrene aromatic rings, whatever the dose range and the irradiation temperature. On the opposite, vinyls are formed only at high ionizing density and are not influenced by excitation transfer; however, their concentration is influenced by radical migration. Highlights: Ethylene/styrene copolymers were irradiated at 11 K and room temperature. Double bonds formation mechanism was studied. Energy and radical migration was evaluated as a function of the double bond nature. Track overlapping effect on double bonds formation was evaluated.